Lingulid brachiopods with probably preserved original shell colouration from the Kamensk Formation (Moscovian, Middle Pennsylvanian) of the Donets Basin, Ukraine - Dernov, Vitaly (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2024)
Problems Statement and Purpose. The colouration (when pigment is distributed more or less uniformly within skeletal substance) and colour patterns (when pigment is concentrated or arranged in bands, lines, spots, patches, etc.) of fossil brachiopod shells is poorly understood, since its preservation in the fossil record requires the coincidence of several, sometimes random, taphonomic factors. However, the study of the original colouration of fossil invertebrates is of great palaeoecological and taphonomic importance (e.g., to study of the evolution of vision, the development of predator-prey relationships). Records of Palaeozoic brachiopod shells with preserved colouration are quite rare and the shell colouration and colour patterns are currently known for only 15 genera. Data and Methods. Studied isolated valves of the lingulid brachiopods Lingularia mytiloides from the lower Moscovian Kamensk Formation of Luhansk Region (Ukraine) show a preserved colour pattern on the outer surface, represented mainly by light concentric bands. Studied remains are represented by small, 8–10 mm long and 6–7 mm wide, moderately convex ventral thin-shelled valves with elongate elliptical outlines, a rounded anterior margin, subparallel lateral margins and a small, pointed umbo. Valve surface is covered with thin concentric growth lines and weakly developed rugae. Results and Discussion. The studied specimens were divided into two groups based on shell colouration features, which may reflect some details of the colouration and colour patterns. However, these differences may be taphonomic artefacts. It is quite possible that the colour bands on the surface of the valves are evidence of sulphide oxidation, but even so, they likely still reflect the original colour patterns. Environmental conditions were important factors for the preservation of the colouration on the shells of the studied lingulid brachiopods. Among these conditions, the most important were slow sedimentation, absence of agents of mechanical and chemical destruction, such as high-energy water activity, encrustation by epibionts, etc., dysaerobic conditions, and rapid burial apparently accompanied by the activity of bacterial communities. The studied colour patterns on the shells of Lingularia mytiloides are similar to those on other fossil lingulids. The adaptive significance of this colouration for the studied lingulids, which lived infaunally, remains unclear and cannot be resolved with the available material.